Validity of Salt Hydrolysis E-Module Based on PBL with Teaching at the Right Level Approach - Parhusip, Efriani Br; Iryani, Iryani (Hydrogen: Jurnal Kependidikan Kimia, 2024)
The Independent Curriculum is an innovation introduced by the Ministry of Education, Indonesia, under regulation No. 56/M/2022. This curriculum concentrates on the core subjects while giving special attention to character development and flexible learning that is adjusted to meet the requirements of individual pupils. One of the chemistry topics in the Independent Phase F Curriculum is salt hydrolysis. The purpose was to determine the level of validation of the PBL-based salt hydrolysis e-module using the TaRL approach. This research employs the Plomp model as part of the educational design research (EDR) framework, encompassing the stages of preliminary research, prototyping, and evaluation, but is limited to Prototype III. This study used five validators to evaluate the module based on language, presentation, content, graphics, and media components using a validation questionnaire.  The results obtained from this study are PBL-based salt hydrolysis e-modules with a valid TaRL approach, with a validation value of the content component of 0.92, presentation of 0.91, language of 0.97, graphics of 0.95, and media average of 0.90.